The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1242/dmm.048931
|View full text |Cite|
|
Sign up to set email alerts
|

ELAC2/RNaseZ-linked cardiac hypertrophy in Drosophila melanogaster

Abstract: A severe form of infantile cardiomyopathy (CM) has been linked to ELAC2 gene mutations. ELAC2 is a highly conserved human gene. It encodes RNaseZL endoribonuclease that plays an essential role in the production of mature tRNAs. To establish a causal connection between ELAC2 variants and CM, here we use a model organism Drosophila melanogaster, which carries ELAC2 homolog - dRNaseZ. Even though dRNaseZ and ELAC2 have diverged in some of their biological functions, our study demonstrates the utility of the fly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 76 publications
2
26
0
Order By: Relevance
“…However, direct correlation between these data and the disease severity observed in patients expressing the variants in question cannot be inferred due to the in vitro nature of these studies. Interestingly, modeling of the p.Phe154Leu and p.Thr520Leu variants in Drosophila showed that, like in humans, expression of the Drosophila orthologs p.Phe155Leu and p.Thre494Ile results in cardiomyopathy [ 31 ]. It remains to be seen, however, if mutagenesis of any of the other amino acids in DmELAC2, which are orthologous to amino acids affected by disease-causing variants in humans, can likewise lead to cardiomyopathy or other pathology in Drosophila.…”
Section: Discussionmentioning
confidence: 99%
“…However, direct correlation between these data and the disease severity observed in patients expressing the variants in question cannot be inferred due to the in vitro nature of these studies. Interestingly, modeling of the p.Phe154Leu and p.Thr520Leu variants in Drosophila showed that, like in humans, expression of the Drosophila orthologs p.Phe155Leu and p.Thre494Ile results in cardiomyopathy [ 31 ]. It remains to be seen, however, if mutagenesis of any of the other amino acids in DmELAC2, which are orthologous to amino acids affected by disease-causing variants in humans, can likewise lead to cardiomyopathy or other pathology in Drosophila.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple structural and functional readouts that have been established for the fly heart can capture these phenotypes. Brightfield microscopy of histological sections or micro computerized tomography, a 3D X-ray imaging technique, can be used to determine the thickness of the heart muscle wall ( Migunova et al, 2021 ; Petersen et al, 2022 ). Whereas high-speed movies of semi intact Drosophila heart preparations ( Ocorr et al, 2007 ), in vivo imaging of the heart in intact flies using high resolution optical coherence microscopy which yields imaging similar to ultrasound ( Migunova et al, 2021 ), or optical coherence tomography which is similar to echocardiography in humans ( Wolf et al, 2006 ), can be used to quantify muscle wall thickness and function, including diastolic diameter, end systolic diameter, and fractional shortening.…”
Section: Drosophila Models Of Myocardial Contractility Dysfu...mentioning
confidence: 99%
“…Brightfield microscopy of histological sections or micro computerized tomography, a 3D X-ray imaging technique, can be used to determine the thickness of the heart muscle wall ( Migunova et al, 2021 ; Petersen et al, 2022 ). Whereas high-speed movies of semi intact Drosophila heart preparations ( Ocorr et al, 2007 ), in vivo imaging of the heart in intact flies using high resolution optical coherence microscopy which yields imaging similar to ultrasound ( Migunova et al, 2021 ), or optical coherence tomography which is similar to echocardiography in humans ( Wolf et al, 2006 ), can be used to quantify muscle wall thickness and function, including diastolic diameter, end systolic diameter, and fractional shortening. Finally, the cardiac flow, a measure of contractile force, can be measured by a dye injection assay that times the flow from injection site to target site ( Zhu et al, 2017a ; 2017b ), or with intravital imaging which enables life tracking of the heart wall, quantitation of the chamber diameter during contraction (systole) and relaxation (diastole), and fractional shortening, as well as estimates of cardiac output and stroke volume using segmentation algorithms ( Klassen et al, 2017 ).…”
Section: Drosophila Models Of Myocardial Contractility Dysfu...mentioning
confidence: 99%
“…Other cardiac disorders have been modelled in D. melanogaster , such as channelopathies [ 163 , 164 , 165 , 166 , 167 ] and different syndromic [ 168 , 169 , 170 ] or nonsyndromic cardiomyopathies [ 171 , 172 , 173 , 174 , 175 , 176 , 177 ]. To our knowledge, currently, none of these diseases benefit from effective human allele-based functional complementation studies, although some groups successfully tackled the heterologous rescuing of fly cardiac phenotype, the alleles of choice being of animal origin, mainly from mice [ 173 , 178 , 179 ].…”
Section: Cardiac Disordersmentioning
confidence: 99%